Improving Understanding of Macrosomia with a Graphics-Based Educational Tool: A Randomized Controlled Trial (MATE) - Cagino, Kristen A.; Kurjee, Myra; Hyde, Emily; Chen, Han-Yang; Mendez-Figueroa, Hector; Chauhan, Suneet P. (American Journal of Perinatology, 2025)
We aimed to determine if a graphics-based education tool (GBET) leads to improved macrosomia knowledge on risk factors/complications (RF/C) and management options (MO) for macrosomia among pregnant individuals compared to routine care.We conducted a randomized control trial (NCTO6281301). Inclusion criteria were individuals at 18 to 55 years, with singleton pregnancy delivering at ≥ 36 weeks. After consent, participants were randomized to either routine care or GBET. To assess knowledge of macrosomia, a questionnaire consisting of 17 questions relating to the RF/C (11 questions) and MO (six questions) of suspected macrosomic fetuses was administered to participants one time either directly after consent (if routine care) or directly following review of GBET. The primary outcome was the overall score on the questionnaire. Secondary outcomes were summary scores on the RF/C and MO. Descriptive statistics were used for baseline characteristics and outcomes. Chi-squared test or Fisher's exact test was used to compare categorical variables and the student's t-test for continuous variables.From January to July 2023, 232 eligible individuals were approached and 196 (84%) agreed to participate; of them, 98 received the GBET, while 98 received routine care. Baseline demographics were similar. The majority (42%) of respondents were non-Hispanic Black, 60% were employed, 56% had some level of college education, and 30% lived below the poverty line. There were 41% nulliparous, 67% with a BMI ≥ 30 kg/m2, and 16% with diabetes. The primary outcome was significantly higher in those who received the GBET (70 vs. 64%; p < 0.001). The RF/C scores were also higher in the GBET group (72 vs. 63%; p = 0.001); however, the MO scores were similar between groups (65 vs. 68%; p = 0.084).In our population, a GBET improved participant knowledge on the RF/C for macrosomia, but not their MO.
Keywords: estimated fetal weight; hemorrhage; macrosomia; shoulder dystocia